2020
DOI: 10.1021/acsnano.0c04165
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of Weakly Bound Proteins Reveals Molecular Basis of Soft Corona Formation

Abstract: Few experimental techniques allow the analysis of the protein corona in situ. As a result, little is known on the effects of nanoparticles on weakly bound proteins that form the soft corona. Despite its biological importance, our understanding of the molecular bases driving its formation is limited. Here we show that hemoglobin can form either a hard or a soft corona on silica nanoparticles depending on the pH conditions. Using cryoTEM and synchrotron-radiation circular dichroism, we show that nanoparticles al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…In addition, they reported the antifouling properties of a zwitterionicfunctionalized NP, where only an SC was formed. Another in situ analysis was performed by Sanchez-Guzman et al [129], where they aimed to reveal the molecular basis of SC formation. In their investigation, the authors investigated the PC formed by hemoglobin on SiNPs.…”
Section: Techniques-in Situ Measurementsmentioning
confidence: 99%
“…In addition, they reported the antifouling properties of a zwitterionicfunctionalized NP, where only an SC was formed. Another in situ analysis was performed by Sanchez-Guzman et al [129], where they aimed to reveal the molecular basis of SC formation. In their investigation, the authors investigated the PC formed by hemoglobin on SiNPs.…”
Section: Techniques-in Situ Measurementsmentioning
confidence: 99%
“…In recent, in situ techniques were employed to character soft corona. For example, a new method using cryoTEM and synchrotron-radiation CD was developed to analyze the weakly bound proteins and reveal molecular basis of soft corona in situ (Sanchez-Guzman et al, 2020). Soft corona proteins were altered by ENPs based on shifting the equilibrium toward the unfolded states at physiological temperature.…”
Section: Characterization Of In Vivo Pc Formationmentioning
confidence: 99%
“…At this point ac ritical discussion is necessary to evaluate the meaning of these results.Afew studies have shown that the protein corona may not change the shape of nanoparticles after protein absorption. This has been demonstrated using liposomes, [34] silica particles [35] and polystyrene particles. [36] However,t hese nanoparticles are either hard and therefore unlikely to deform, or they do not have ahairy surface where proteins may entangle.I ti st herefore reasonable to believe that hairy and soft nanoparticles may indeed undergo ashape change triggered by the tension in the shell.…”
Section: Methodsmentioning
confidence: 99%